K probleme farmakologicheskogo obespecheniya myshechnoi deyatel'nosti - Makarova, G. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
Position to the pharmacological support of the muscular activities in high performance sports. What is the best way for the whole organism to solve this problem ? Which principles should be followed? The different groups of pharmaka to stimulate the muscle activity are explained.